Reduction behavior of insecticide azoxystrobin and its voltammetric determination using silver solid amalgam electrode - Šelešovská, Renáta; Herynková, Marie; Skopalova, Jana; Kelíšková, Pavlína; Janíková, Lenka; Chýlková, Jaromíra (Springer, 2019)
Electrochemical reduction of systemic fungicide azoxystrobin, used to protect a wide variety of crops, was investigated using cyclic voltammetry with a mercury meniscus-modified silver solid amalgam electrode (m-AgSAE). The mechanism of the electrochemical reduction was proposed and supported with high-performance liquid chromatography/mass spectrometry analysis of azoxystrobin solutions electrolyzed on mercury pool electrode. An analytical method for the determination of azoxystrobin by differential pulse voltammetry with m-AgSAE was developed. A wide linear dynamic range (2.0x10(-6)-5.0x10(-5)moldm(-3)) and low limit of detection (7x10(-7)moldm(-3)) were obtained. The accuracy and repeatability of the proposed method were evaluated by the analysis of model solutions with recovery from 96.0 to 104.0% and relative standard deviation of 5 repeated determinations<3.5%. Finally, a new voltammetric method using m-AgSAE was successfully applied for azoxystrobin determination in real samples, concretely in spiked river water and pesticide preparations. [GRAPHICS] .
Redukční chování insekticidu azoxystrobinu a jeho voltametrické chování s využitím stříbrné pevné amalgámové elektrody
Keywords: Pesticides; Azoxystrobin; Reduction mechanism; Voltammetric determination; Silver solid amalgam electrode; Pesticidy; Azoxystrobin; Redukční mechanismus; Voltametrické stanovení; Stříbrná pevná amalgámová elektroda